Rafaelomyia, a remarkable new genus of South American long-legged flies (Diptera, Dolichopodidae) - Soares, Matheus M. M.; Capellari, Renato S.; Ramos-Pastrana, Yardany (Zootaxa, 2023)
A new dolichopodid genus (Diptera, Dolichopodidae), Rafaelomyia Soares, Capellari & Ramos-Pastrana gen. nov., is described and comprises the following five new species from Northern South America: Rafaelomyia exu Soares & Capellari sp. nov. (Cusco, Peru), R. inpa Soares, Capellari & Ramos-Pastrana sp. nov. (Cusco, Peru), R. singularis Soares & Capellari sp. nov. (Cusco, Peru), R. uniamazonia Ramos-Pastrana & Soares sp. nov. (Huila, Colombia), and R. xavieri Soares & Capellari sp. nov. (Cusco, Peru). The new genus is tentatively placed in the subfamily Sympycninae based on a suite of characters traditionally associated with the subfamily: head ovate on anterior view (antenna on top of head), wing with “bosse alaire”, vein M unbranched into M1 and M2, tibia I with anterodorsal row of setae, male abdomen not pedunculated, with setose tergite 6 and male hypopygium relatively small, despite the lack of anterior preapical setae on femur II and/or III and the presence of a conspicuous flattened posterior slope of mesonotum. The systematic position of the new genus is discussed and an identification key to males is provided.